Evaluation of the Impact of Financial Report Quality, Auditor Independence, and the Use of Audit Technology on Client Satisfaction at Public Accounting Firms in Jakarta - Judijanto, Loso; Sudarmanto, Eko (Westscience Press, 2024)
This research investigates the intricate dynamics influencing client satisfaction at public accounting firms in Jakarta. Employing a quantitative approach, a survey methodology with 150 clients was utilized to evaluate the impact of financial statement quality, auditor independence, and the use of audit technology on client satisfaction. The data was analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). Descriptive statistics, measurement model evaluation, structural model analysis, and discriminant validity assessments were conducted to comprehensively understand the relationships between the variables. The model fit indices indicated a strong alignment between the estimated and saturated models, affirming the reliability and validity of the research model. Hypothesis testing results demonstrated that auditor independence, financial report quality, and the use of audit technology significantly influence client satisfaction in the Jakarta context. The findings contribute to both academic literature and practical implications for public accounting firms seeking to enhance client relationships.